2014
DOI: 10.1227/neu.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Field Intraoperative Magnetic Resonance Imaging to Enhance the Extent of Resection of Enhancing and Nonenhancing Gliomas

Abstract: IoMRI enhances the extent of resection, particularly for nonenhancing gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Use of intraoperative MRI and intraoperative fluorescence-guided surgery with 5-ALA may potentially allow for more complete resection. 172,173 One exception is when CNS lymphoma is suspected; a biopsy should be performed before steroids are administered, and management should follow the corresponding pathway if the diagnosis is confirmed. When maximal resection is performed, the extent of tumor debulking should be documented with a postoperative MRI scan with and without contrast performed within 48 hours after surgery.…”
Section: Primary Treatmentmentioning
confidence: 99%
“…Use of intraoperative MRI and intraoperative fluorescence-guided surgery with 5-ALA may potentially allow for more complete resection. 172,173 One exception is when CNS lymphoma is suspected; a biopsy should be performed before steroids are administered, and management should follow the corresponding pathway if the diagnosis is confirmed. When maximal resection is performed, the extent of tumor debulking should be documented with a postoperative MRI scan with and without contrast performed within 48 hours after surgery.…”
Section: Primary Treatmentmentioning
confidence: 99%
“…Intra-operative MRI appears to be an important tool that allows neurosurgeons to maximize the extent of surgical resection of gliomas, particularly for lower grade (non-enhancing) tumors [17]. Many studies have shown various advantages of IoMRI in surgical management of brain tumors, including its safety [11, 15, 2428].…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival (OS) will depend on several factors including Karnofsky performance status (KPS), age, tumor extension, neurological deficit, molecular or genetic markers, extent of resection (EOR), and chemoradiation treatment [17,18]. It is established that one of the modifiable factors for survival in HGG is the EOR but also the residual tumor volume left after surgery [19][20][21]. Therefore, the current standard of care involves a multidisciplinary approach including maximal safe tumor cyto-reduction with subsequent chemotherapy and radiation [22].…”
Section: Litt In Gliomasmentioning
confidence: 99%